Imitation of MSME Transaction Documents as a Form of Business Identity Misuse: A Socio-Legal Analysis of the Gap Between Norms and Practices - Eghi Hendri Rifaldo Purba; Martono Anggusti; Samuel Frans Boris Situmorang (Journal of Legal and Cultural Analytics, 2026)
The counterfeiting of Micro, Small, and Medium Enterprise (MSME) transaction documents—a form of business identity misuse—is a crime that has emerged alongside the accelerated digital transformation of economic activities. This study aims to comprehensively analyze the gap between legal norms (*das sollen*) and social practices (*das sein*) regarding the protection of MSME business identities, employing a socio-legal approach. The research methodology combines a normative-juridical approach with a socio-legal perspective. This approach views law not merely as written norms ("law in the books") but also as social practices operating within society ("law in action"). Research data were gathered through a literature review of primary, secondary, and tertiary legal materials, alongside an analysis of digital transaction document usage patterns within the MSME ecosystem. The findings reveal a significant legal gap in the protection of MSME business identities in the digital era. Normatively, Indonesian law provides instruments to address document forgery and the manipulation of electronic information. Empirically, however, the effectiveness of these measures is severely limited by the high costs associated with digital evidence, the complexity of electronic forensic processes, and the absence of an integrated, affordable, and easily accessible business identity verification system for MSME players. Consequently, existing legal protections remain largely formalistic and fail to fully address the needs of the small-scale economic community.